2005
DOI: 10.1111/j.1365-2567.2005.02276.x
|View full text |Cite
|
Sign up to set email alerts
|

A canine model of cutaneous late‐phase reactions: prednisolone inhibition of cellular and cytokine responses

Abstract: SummaryImmunoglobulin E (IgE)-mediated late-phase reactions can be induced in atopic humans by intradermal injection of relevant allergens or anti-IgE antibodies. The histology of these reactions resembles that of naturally occurring atopic dermatitis. Strikingly similar responses can be induced in dogs, suggesting that a canine model could prove valuable for preclinical investigation of drugs targeting late-phase reactions. This study was designed to characterize the cellular, cytokine and chemokine responses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
63
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(68 citation statements)
references
References 54 publications
5
63
0
Order By: Relevance
“…The anti-IgE injection resulted in increased numbers of CD3 + cells, compared with the number of CD3 + cells after IgG injection, from 20 minutes to 24 hours with a subsequent decrease in cell counts at 48 hours, but these values did not differ significantly ( Figure 5). This pattern was similar to that for a previous study 9 in dogs in which CD3 + cells increased by 6 hours and peaked 24 hours after anti-IgE injection. Another study 8 conducted to evaluate late-phase reactions after ID injection of anti-IgE in dogs found that dermal counts of CD3 + cells increased from 6 to 48 hours after injection.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The anti-IgE injection resulted in increased numbers of CD3 + cells, compared with the number of CD3 + cells after IgG injection, from 20 minutes to 24 hours with a subsequent decrease in cell counts at 48 hours, but these values did not differ significantly ( Figure 5). This pattern was similar to that for a previous study 9 in dogs in which CD3 + cells increased by 6 hours and peaked 24 hours after anti-IgE injection. Another study 8 conducted to evaluate late-phase reactions after ID injection of anti-IgE in dogs found that dermal counts of CD3 + cells increased from 6 to 48 hours after injection.…”
Section: Discussionsupporting
confidence: 90%
“…[10][11][12][13][14][15][16] In dogs, a model of allergic dermatitis has been successfully developed by the use of anti-IgE. 8,9 To our knowledge, such a model of allergic dermatitis in horses has not been developed.…”
Section: Anti-igementioning
confidence: 99%
See 1 more Smart Citation
“…In this model, pruritus and dermatitis can be elicited after epicutaneous application of house dust mites [75]. Lesions are consistent with naturally occurring AD lesions [76,77] making it a suitable model to test new therapies. No skin barrier defect has been described in this model compared to a control population.…”
Section: Dog Models Of Atopic Dermatitismentioning
confidence: 99%
“…Probably, they rather depend on the newly synthesized late products of the activated mast cells such as leukotrienes and prostanoids [17] as well as the modulation of the mainly neutrophilic as well as eosinophilic infiltrate of type 1 late-phase reactions [18]. Consistently, the leukotriene antagonist (LT-A) montelukast was shown not to affect or influence the immediate response of skin tests with allergen [19], while repressing, for example, delayed pressure urticaria [20].…”
Section: Introductionmentioning
confidence: 99%